mGluR5/ERK signaling regulated the phosphorylation and function of glycine receptor α1ins subunit in spinal dorsal horn of mice. - Zi-Yang Zhang; Hu-Hu Bai; Zhen Guo; Hu-Ling Li; Yong-Tao He; Xing-Lian Duan; Zhan-Wei Suo; Xian Yang; Yong-Xing He; Xiao-Dong Hu (PLoS Biology, 2019)
Inhibitory glycinergic transmission in adult spinal cord is primarily mediated by glycine receptors (GlyRs) containing the α1 subunit. Here, we found that α1ins, a longer α1 variant with 8 amino acids inserted into the intracellular large loop (IL) between transmembrane (TM)3 and TM4 domains, was expressed in the dorsal horn of the spinal cord, distributed at inhibitory synapses, and engaged in negative control over nociceptive signal transduction. Activation of metabotropic glutamate receptor 5 (mGluR5) specifically suppressed α1ins-mediated glycinergic transmission and evoked pain sensitization. Extracellular signal-regulated kinase (ERK) was critical for mGluR5 to inhibit α1ins. By binding to a D-docking site created by the 8-amino-acid insert within the TM3-TM4 loop of α1ins, the active ERK catalyzed α1ins phosphorylation at Ser380, which favored α1ins ubiquitination at Lys379 and led to α1ins endocytosis. Disruption of ERK interaction with α1ins blocked Ser380 phosphorylation, potentiated glycinergic synaptic currents, and alleviated inflammatory and neuropathic pain. These data thus unraveled a novel, to our knowledge, mechanism for the activity-dependent regulation of glycinergic neurotransmission.